A Philosophy of Open Digital Badges - Flintoff, K.; Willis, J.; McGraw, B.; Flintoff, Kim (Springer International Publishing, 2016)
One of the most promising educational technology tools, open digital badges, is quickly changing curricula, job acquisition, and workforce credentialing. Learning data, assessments, and expert validation made accessible in social media create a transparency that may well be suited for critical questions in education. Operating from a framework of establishing how badges are currently employed in learning—the influential contexts of individuals and communities, and data aggregation—raises questions concerning the roles of instructors, badge providers, and learning management systems. This “philosophy” of digital badges addresses a variety of epistemological concerns including the intersection of challenges to conventional educational motivation, suggestions of how Platonic and modern models of education are complementary, and implications of how badges may represent postmodern credentialing systems. These concerns are framed around understanding how current work in digital badges can feasibly transform learning; this is both an acknowledgment of how badges are beginning to change ecosystems of informal and formal learning as well as an attempt to demonstrate how an epistemological philosophy of badges can change educators’ thinking and accelerate innovation.